Chikungunya Particle and RNA Induce Mechanical and Heat Hypersensitivities in a TRPV1-Dependent Manner - Liziane C. M. da Silva; Andressa C. dos Santos Maia; Nágila C. F. de Sousa; Catielen P. Pavi; Beatriz P. Savi; Seigo Nagashima; Samara Damasceno; Ayda H. Schneider; Lucas Z. Mascarin; João F. S. Rodrigues; Cinara R. A. V. Monteiro; Izabella T. Silva; et al. (Biomolecules)
Chikungunya virus (CHIKV), the causative agent of the chikungunya fever, is an alphavirus widely transmitted by the bite of the female mosquito of the genus Aedes sp., especially in tropical and subtropical regions. Brazil is the country most affected by the microorganism. CHIKV classically induces articular pain, which can become long lasting for even years in a great number of the infected individuals, reducing their quality of life. The mechanisms of CHIKV-induced pain are poorly understood, but recent evidence indicated a role for the transient receptor potential vanilloid 1 (TRPV1) in this pathology. Herein, we assessed the ability of intra-articularly injected inactivated CHIKV or its RNA to trigger nociception in mice. Both stimuli induced bilateral secondary hyperalgesia to mechanical and heat stimuli. These responses were attenuated by TRPV1 ablation or antagonism. Joint structural alterations and increased cartilage TRPV1 protein expression were detected in the ipsilateral knee joints injected with either CHIKV or viral RNA. However, the lack of this receptor did not influence the histological changes triggered by CHIKV or RNA. The results further support the role of TRPV1 in CHIKV-induced pain and highlight its importance in the chronic phase of the disease.